Multimodal Displays to Reduce Distraction In Locomotive Engineers. (December 2020) - Grice, Rachel; Fisher, Donald; Isaacs, Matthew; Liu, Andrew
Multi-modal displays that allow the locomotive engineer to delay safety-critical dispatches in high workload scenarios offer the promise of reducing the cognitive distraction that occurs when the locomotive engineer must listen to a dispatcher's communication. In an effort to determine whether locomotive engineers could delay safety-critical information from the dispatcher in high workload scenarios, we developed and evaluated such a multi-modal display system. It was hypothesized that locomotive engineers, when provided with the ability to postpone the delivery of information from the dispatcher, would perform better than locomotive engineers who were not provided that capability. Contrary to the above hypothesis, an analysis of the eye tracking measures indicated that the engineers performed more poorly in the multi-modal display system condition, indicating that the system as designed did not allow the engineer to safely delay dispatch messages. We conclude that aspects of the new system that seemed to increase distraction should be redesigned to modify how and when the engineer uses the system to access information and allow for a safe delay of safety-critical information.